Interval-Valued Fuzzy Cognitive Maps for Supporting Business Decisions - Hájek, Petr; Procházka, Ondřej (IEEE (Institute of Electrical and Electronics Engineers), 2016)
Fuzzy cognitive maps (FCMs) are used to model uncertainty in complex causal relationships among concepts. This is an important issue for supporting business decisions. However, determining the precise values of these relationships is difficult in the domain of business decision-making. To overcome this problem, we introduce interval-valued FCMs representing a generalization of FCMs. Interval-valued FCMs provide desirable additional freedom in the design of concepts and their causal relationships. This feature enables decision makers to model highly complex business decision-making problems. We demonstrate this for two case studies: (1) a supplier-selection task, and (2) business-performance modelling.
Intervalově ohodnocené fuzzy kognitivní mapy pro podporu podnikového rozhodování
Keywords: Business; Decision-making; Fuzzy cognitive maps; Interval-valued fuzzy sets; Podnik; rozhodování; fuzzy kognitivní mapy; intervalově ohodnocené fuzzy množiny